2021
DOI: 10.1016/j.abd.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous smooth muscle tumors associated with Epstein-Barr virus in an adult patient with HIV

Abstract: Epstein Barr virus-associated smooth muscle tumors are an uncommon neoplasm that occurs in immunosuppressed patients of any age. Usually, it presents as multifocal tumors mainly in the spinal cord, epidural region, gastrointestinal tract and liver, upper respiratory tract and skin, the latest with few cases reported in the literature and related with human immunodeficiency virus infection and acquired immune deficiency syndrome. The authors present the first case of a Colombian adult patient with human immunod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…A study by Deyrup et al examined EBV-SMTs in 19 patients with multiorgan involvement and found that, in each case, the tumors were genetically distinct, suggesting that the multiorgan condition arises from multiple primary tumors rather than metastasis [59]. Moreover, it has been observed that EBV-SMTs related to HIV infection tend to have a higher likelihood of central nervous system involvement [25][26][27]29,31,35,43,45,52,59].…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%
“…A study by Deyrup et al examined EBV-SMTs in 19 patients with multiorgan involvement and found that, in each case, the tumors were genetically distinct, suggesting that the multiorgan condition arises from multiple primary tumors rather than metastasis [59]. Moreover, it has been observed that EBV-SMTs related to HIV infection tend to have a higher likelihood of central nervous system involvement [25][26][27]29,31,35,43,45,52,59].…”
Section: Ebv-associated Smooth Muscle Tumorsmentioning
confidence: 99%